2020
DOI: 10.1186/s41938-020-00303-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of indigenous plant growth-promoting rhizobacteria and Trichoderma strains in eliciting resistance against bacterial wilt in a tomato

Abstract: Bacterial wilt of tomato caused by Ralstonia solanacearum is a serious threat to tomato production worldwide. For eco-friendly management of bacterial wilt of tomato, the rhizospheric microorganisms belonging to the genera Bacillus (6 isolates), Brevibacillus (1 isolate), Pseudomonas (3 isolates), and Trichoderma (8 isolates) were studied for their ability to induce innate immunity in tomato, individually and in combination against R. solanacearum in greenhouse and field studies. In laboratory studies, maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Inoculation of T. asperellum Tc-Jjr-02 at six hours before and after and simultaneously with pathogens provided protection (reducing the symptom index by 56-63%) for young tobacco plants against tobacco bacterial wilt disease caused by R. solanacearum (Jalaluddin et al, 2021). Previous studies (Konappa et al, 2020, Konappa et al, 2018, Mohamed et al, 2020 also revealed a reduction of potato and tomato wilt, caused by Ralstonia solanacearum (Smith) by T. asperellum isolate under greenhouse and field conditions. Even leaf spray of T. asperellum also reduced the growth of bacterial spots on tomato caused by Xanthomonas (Chien and Huang, 2020).…”
Section: In Planta Antagonism Assaymentioning
confidence: 79%
See 1 more Smart Citation
“…Inoculation of T. asperellum Tc-Jjr-02 at six hours before and after and simultaneously with pathogens provided protection (reducing the symptom index by 56-63%) for young tobacco plants against tobacco bacterial wilt disease caused by R. solanacearum (Jalaluddin et al, 2021). Previous studies (Konappa et al, 2020, Konappa et al, 2018, Mohamed et al, 2020 also revealed a reduction of potato and tomato wilt, caused by Ralstonia solanacearum (Smith) by T. asperellum isolate under greenhouse and field conditions. Even leaf spray of T. asperellum also reduced the growth of bacterial spots on tomato caused by Xanthomonas (Chien and Huang, 2020).…”
Section: In Planta Antagonism Assaymentioning
confidence: 79%
“…Even leaf spray of T. asperellum also reduced the growth of bacterial spots on tomato caused by Xanthomonas (Chien and Huang, 2020). In addition to disease reduction, T. asperellum also enhanced tomato seed germination, fruit yield, plant growth and increased the dry weight of plant biomass promotion under field conditions (Konappa et al, 2020, Jalaluddin et al, 2021.…”
Section: In Planta Antagonism Assaymentioning
confidence: 96%
“…In Mirikaria, the best preparation affecting the increase in the diameter of the root neck was Black yeast: 5.6; 6.6; 8.8; 9.1 mm (Fig. 6,7,8,9).…”
Section: Resultsmentioning
confidence: 99%
“…These are primarily antibiotics with a pronounced fungicidal effect, which inhibit the development of many pathogens and inhibit their reproductive capacity. The use of these microscopic fungi has given positive results in various agricultural crops due to their high antagonistic ability [7][8][9]. The use of yeast as plant growth promoting agents is underutilized.…”
Section: Introductionmentioning
confidence: 99%
“…Many other fungi and bacteria are endophytic and can potentially be used for seed treatment. These include fungi in the genera Trichoderma (Harman 2011;Woo et al 2014;Doni et al 2017), Aspergillus (Ismail et al 2020), Penicillium (Ikram et al 2018a), Clonostachys (Shafia et al 2001), Piriformaspora (Sherameti et al 2005), and Yarrowia lipolutoca (Franza et al 2019), as well as bacteria in the genera Pseudomonas (Konappa et al 2020) and Bacillus (Konappa et al 2020;Brannen 1997), and in the family Rhizobiacae (Chi et al 2015).…”
Section:  Endophytic and Rhizopheric Competencementioning
confidence: 99%